THE INFLUENCE OF THE PREOPERATIVE PRELOAD WITH CARBOHYDRATES UPON METABOLIC, IMMUNE AND CYTOKINE STATUSES AFTER RECONSTRUCTIVE ESOPHAGEAL SURGICAL INTERVENTIONS - I. A. Tarasova (SPb RAACI, 2018)
The aim of this prospective randomized clinical study was to investigate the role of preoperative carbohydrate admnistration in surgery-induced metabolic, immune and inflammatory reactions after thoracoabdominal operations. At the Surgical department I (B.V. Petrovsky National Research Center of Surgery), we investigated a modulatory role of carbohydrate preload upon surgical stress observed after major thoracoabdominal operations (thoracoscopic and open esophagectomy, retrosternal colonic esophagoplasty) followed by the enhanced recovery protocol. The study was performed in 2014-2017, it included 30 patients, divided into 2 groups. Group A patients (n = 16) received carbohydrates preload (12.5% maltodextrin solution per os or enterally). In patients with dysphagia, the 12.5% dextrose solution was used intravenously in equal volumes. Group B patients didn’t receive any additional preload with carbohydrates. The groups were age- and gendermatched, similar for disease and surgery types. Glucose and insulin levels (with HOMA insulin resistance index, HOMA-IR) were measured before surgery and on day +1, interleukin levels (IL-6, IL-10, IL-8) and index IL-8/IL-10 were assessed before surgery, and on days +1 and +5 after surgery. Cell-mediated immunity was investigated before surgery and on day +5.The stress-induced hyperglycemia (> 7.8 mmol/L) was detected more frequently in group B (50%), than in group A (6%), p = 0.012. Insulin resistance measured by HOMA-IR in group B was detected in 71% of patients and in 25% patients of group A only, p = 0.027. Individual analysis of immune response demonstrated that a trend for immune recovery was detected by the day +5 post-op in the group A. Postoperative levels of IL-6 and IL-10 were lower on day +1 and +5 in group A. Morbidity rates and the terms of hospitalization were similar in both groups. Local postsurgical infections in group A were developed in 6% of the patients vs 35.6% in group B (p = 0.072).In conclusion, a complex study of surgical stress, i.e., metabolic, immune and inflammatory reactions after esophageal surgery has shown that the carbohydrate preload decreased the incidence of postoperative insulin resistance and stress-induced hyperglycemia, being accompanied by lower release of proinflammatory cytokines and provides positive effects upon the patient’s immune system.